ROLE OF DEMOGRAPHIC FACTORS THROUGH CUSTOMER LOYALTY IN BUILDING CUSTOMER’S SATISFACTION - Ariffin, IA; Hamid, Junainah Abd; Shukri, , Shakeerah Mohd (International Journal of Psychosocial Rehabilitation, 2020)
This study will investigate and explore between independent variables, and dependent variable which consist of several factors that influence burger’s quality in Selangor, Malaysia which affect customer’s satisfaction. The research explain the relationship based on demographics of customers through their loyalty towards customer satisfaction. The findings for demographic factors indicate that there is significant difference in customer loyalty. The increase perception on age of customer will influence positively to customer loyalty which in turn enhances the satisfaction of the customers.